EDUKASI HIPERKOLESTEROLEMIA DI POSYANDU LANSIA KEMBANG SEPATU, WILAYAH KERJA PUSKESMAS BANJARBARU SELATAN - Mardiati, Nurul; Ignasia , Johanna; Kurniasih, Endang (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Cholesterol is a yellowish fat molecule that resembles wax which is produced by the liver and circulated throughout the body through the blood vessels. Hypercholesterolemia can occur when LDL (Low Density Lipid) levels are higher than HDL (High Density Lipid) levels. This health education activity aims to increase public knowledge and understanding, especially in the South Banjarbaru Community Health Center, regarding hypercholesterolemia including signs and symptoms, how to use drugs, and prevention. The activity includes several stages, namely the presentation of material using the lecture method and leaflet media, question and answer session, pretest and post test. The percentage result of the pretest average score is 51.4286% and the post test average is 97.1429%. This research concludes that there is an increase in community knowledge of the elderly posyandu after being provided with education and exposure to material related to cholesterol.